CENTRAL PART OF DNIEPER-DONETS BASIN: RESERVOIR PROPERTIES OF DEEP-LAID TERRIGENOUS ROCKS - Rybalka, S.; Karpenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Estimating oil and gas reserves is irrelevant without exploring lower boundary environment of reservoir rocks, which directly affect the capacity of hydrocarbon reserves. The increasing depth of the productive sediments is known to naturally derate porosity, permeability, and clay content. In the case of three central fields of the Dnieper-Donets basin there are given statistical patterns of porosity and permeability distribution relative to depth of rocks. Core material from the deposits that follow became the actual samples for statistical and laboratory analysis: 148 samples from the Semyrenkivske field, 98 samples from the Kaverdynske field, and 370 samples from the Komyshnyanske field, namely. Statistical analysis shows significant variations in the ratio of porosity within the adopted permeability limit values (0.8-1.0 fm2). The range of Kn values of Kpor varies from 0.1% to 13%. Accordingly, the use of only one threshold value (Kpor lim) can result in false conclusions about the filtration and capacitive properties of individual layers. Inherent fracture permeability and porosity, which is indicative of deep-laid reservoir rocks, provides good filtration and capacitive properties of producing strata, making greater depths a promising direction for further prospection for and development of hydrocarbon deposits.